At morning's light - Snelling, Lauraine; Giron, Kiersti (Home to Green Creek, 2025)
"In 1890 Norway, newlywed Maya's dreams are crushed when a fierce winter storm steals her husband away before their voyage to America. Though anguish and grief engulf her, she travels to Iowa, where her new neighbor, Eben Miller, seeks to help mend her broken heart. Can they weather these trials together and overcome the difficulties this land holds?"--